ANALISIS PRIORITAS KEPUTUSAN KONSUMEN DALAM MEMILIH COFFEE SHOP MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS - NI GUSTI AYU KADEK SARI PURNAMAYANTI; I KOMANG GDE SUKARSA; G. K. GANDHIADI; I PUTU EKA NILA KENCANA (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
This study aims to determine the priority weights of criteria and sub-criteria, as well as the priority order of coffee shop alternatives based on consumer preferences using the analytic hierarchy process (AHP) method. This study involved 50 respondents consisting of three groups: 5 expert respondents, 30 active respondents, and 15 passive respondents. The hierarchical structure was compiled based on the 4P Marketing Mix framework, which includes four main criteria: product quality, price, location, and promotion, with three sub-criteria each. The three alternatives compared were Kopi Kenangan, Fore Coffee, and Point Coffee. The results of the study from all respondents showed that Price was the criterion with the highest priority weight (0.358), followed by Product Quality (0.237), Promotion (0.213), and Location (0.189). In terms of alternative priorities, Kopi Kenangan ranked first (0.402), Fore Coffee ranked second (0.335), and Point Coffee ranked last (0.261). These findings can serve as a reference for businesses in increasing their competitiveness.